MODELING OF CURRENT LIMITATIONS IN PHOTO-ELECTRICAL SYSTEMS OF SOLAR BATTERIES USING SELF-RESTORING FUSES POLYSWITCH - Tonkoshkur, A. S.; Nakashidze, L. V. (Radio Electronics, Computer Science, Control, 2019)
Context. Solving the problem of increasing the reliability of solar cells, including the elimination of abnormal (fire hazardous) situations based on the development of methods and means to prevent current overloads in their photovoltaic systems. Objective. The study of the prospects of minimizing current overloads in photovoltaic systems of solar cells through the use of low-cost elements of functional electronics in particular rather new and widely used self-healing fuses of the type “Polyswith”. Method. A circuit design is proposed and the modeling method makes it possible to use Polyswitch-type fuses to prevent and minimize current overloads in photovoltaic solar panels. Results. The influence of the magnitude of the resistance in the conducting state and the current of operation of the fuses on the current-voltage and voltage-watt characteristics of parallel connections of photoelectric converters and their modules is analyzed. Conclusions. It is shown that an effective current limitation in the presence of short-circuits with such a connection of photovoltaic components can be realized under the following conditions: – the resistance of the fuse in the conducting state is much less than the consistent resistance of the photoelectric component; – the current of the fuse should be greater current of short circuit of a separate photoelectric component and less current of their parallel connection.